Menakar Nalar Pendidikan Pesantren Berbasis Kearifan Lokal - Nurlaela, Andi (Universitas Nurul Jadid, 2018)
This study is to figure out the possibility of pesantren in designing a local wisdom based logics of education. It is a starting hypothesis that needs more analysis, theory, and discussion. Today’s globalisation often makes pesantren into a streotypical ‘scary’ position among society, then it needs an escalation from trom self-developmental educational system into a logics of education which is based on tolerances and local wisdom. This effort is possible to do with habituation of local wisdom based logics of education to santri. The possible solution is getting started with the simplest thing instead of underestimating the dominant globalisation and traditional nature of pesantren.